The responsibility to protect (R2P): an analysis of the fulfillment of the obligation borne by the Nigerian Government and the international community to protect the Nigerian population from Boko Haram - Hatupopi, Petrus (Department of Public Law, 2018)
This dissertation investigated the doctrine of the responsibility to protect (R2P), which was unanimously endorsed at the 2005 UN World Summit by all the UN Member States. I determined the status of R2P in public international law. I found that, although the 2005 UN World Summit Outcome Document is not a source of international law, the responsibility to protect contained therein under paragraph 138, reiterated the existing international legal obligation of states to protect their populations from genocide, crimes against humanity, war crimes and ethnic cleansing. I have argued that if a state fails to fulfil its legal obligation to protect its population from mass violations of human rights, the principle of state sovereignty and its accompanying norm of non-intervention cannot prevent the international community from responding appropriately to protect the population of that state. But the international community does not have a legal obligation on how it should respond to situations of human rights violations. However, the responsibility to protect as contained in paragraph 139 of the 2005 UN World Summit Outcome Document and the constitutive documents of organizations such as the United Nations, the African Union and the Economic Community of West African States (ECOWAS) have given authority to the international community to intervene in their member states in order to protect populations from mass atrocity crimes. On that basis, the responsibility to protect on the part of the international community exists. But the international community retains the discretion to decide on whether it should respond and how it should react to situations that fall within the scope of R2P. I used the three pillars of the responsibility to protect, contained in the 2009 report of the UN Secretary General to determine how the responsibility to protect was implemented in Nigeria to protect the population from crimes against humanity and war crimes perpetrated by members of the Islamic extremist militant group called Boko Haram. I analyzed various measures taken by the Nigerian government, the United Nations, the African Union, and the Economic Community of West African States (ECOWAS) and concluded that the measures taken were not effective in defeating Boko Haram. Hence, I found that the responsibility to protect was not successfully implemented in Nigeria.